2007
DOI: 10.1634/stemcells.2006-0731
|View full text |Cite
|
Sign up to set email alerts
|

Thoracic Aortas from Multiorgan Donors Are Suitable for Obtaining Resident Angiogenic Mesenchymal Stromal Cells

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
111
0
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 121 publications
(118 citation statements)
references
References 34 publications
5
111
0
2
Order By: Relevance
“…2 As discussed in the following sections, these consist of lineage-committed endothelial progenitor cells (EPCs) 4 and smooth muscle progenitor cells (SPCs), 5,6 multipotent vascular stem cells (MVSCs), 7 mesenchymal stem/stromal cells (MSCs), 8,9 adventitial macrophage progenitor cells (AMPCs), and circulation-derived HSCs. 10,11 …”
Section: Vw-pcs Vascular Wall Progenitor Cellsmentioning
confidence: 99%
“…2 As discussed in the following sections, these consist of lineage-committed endothelial progenitor cells (EPCs) 4 and smooth muscle progenitor cells (SPCs), 5,6 multipotent vascular stem cells (MVSCs), 7 mesenchymal stem/stromal cells (MSCs), 8,9 adventitial macrophage progenitor cells (AMPCs), and circulation-derived HSCs. 10,11 …”
Section: Vw-pcs Vascular Wall Progenitor Cellsmentioning
confidence: 99%
“…Adventitial cells participate in vascular growth and repair and are important determinants of lumen size via control of inward or outward wall remodeling processes (2,5). Recent studies report unexpected roles for the adventitia insofar as it supports resident progenitor cells that can adopt both vascular and nonvascular fates (6)(7)(8). Despite these important functional properties, the signals and environmental cues that confer such unique and dynamic properties to the adventitial layer remain largely unknown.…”
mentioning
confidence: 99%
“…The adventitia responds to balloon catheter injury with rapid increases in SM␣Actin and SM22␣ expression, particularly at the media-adventitia interface (5). Endothelial progenitor cells are reported to cluster between the media and adventitia in human arteries (7,8). These cells formed capillary sprouts in ex vivo ring culture assays and were recruited by tumor cells for capillary vessel formation in vivo.…”
mentioning
confidence: 99%
“…Early studies demonstrated that MSCs formed capillary-like structures, composed of an endothelial tube covered by PCs. 40,41 Most MSCs prepared in these studies are composed of heterogenous cell populations that may contain endothelial-and PC-progenitor cells or pluripotent stem cells. 42 In this study, clonal mPCs acquired both endothelial-and PC-like phenotypes in the presence of VEGF and formed capillary-like structure on their own in Matrigel ( Figure 6).…”
Section: Mpcs Are Capillary-forming Stem Cellsmentioning
confidence: 99%